Optimized Liveness Detection for Fast and Accurate Fingerprint Anti-Spoofing With Optical Coherence Tomography - Yilong Zhang; Heyou Yu; Haohao Sun; Yongbo Yao; Haixia Wang; Jian Liu; Yuanjie Dang; Ronghua Liang; Peng Chen (IEEE Photonics Journal)
Optical coherence tomography (OCT) offers high-resolution imaging of internal finger structures, making it attractive for fingerprint recognition. Anti-spoofing research in OCT includes both static and liveness anti-spoofing. Liveness anti-spoofing is commonly detected by additional detection equipment or by extracting the liveness information from the OCT data. However, previous methods suffer from long data acquisition and computation times as well as low recognition accuracy. To address these problems, this paper proposes a fast liveness anti-spoofing method. The method requires no additional detection equipment, is fast in data acquisition and calculation, and has high computational accuracy. This study not only explores the method's effectiveness but also performs parameter analysis and optimization on multiple scales. In addition, this paper presents a comprehensive mathematical model that enables various types of OCT devices to calculate the optimal anti-counterfeiting parameters under different conditions. The experimental results show that this method can substantially improve the accuracy and real-time performance of anti-spoofing, and applies to various types of OCT systems, has a promising application in fingerprint identification and other medical diagnostic fields.